Impact of Iron and Vitamin B 12 Deficiency on Hemoglobin Levels and Complete Blood Count Indices: A Laboratory-Based Study in Surman , Libya (Comprehensive Journal of Science, 2026)
Iron deficiency remains the leading global cause of anemia; however , the relative contribution of vitamin B 12 deficiency varies acro ss populations , This laboratory-based cross-sectional study evaluated the association between ferritin , vitamin B 12 , and hemoglobin levels among 150 anemia cases identified from Surman Central Laboratory records in Surman , Libya , Microcytosis was the dominant hematological pattern ( mean MCV = 79.83 fL ) , Multivariate regression revealed that ferritin was independently associated with hemoglobin ( β = 0.412 , p < 0.001 ) , whereas vitamin B 12 showed no significant effect , The model explained 17.1 % of hemoglobin variance , These findings highlight iron deficiency as the principal determinant of anemia in this setting.
Keywords: Iron deficiency anemia; Vitamin B 12 deficiency; Hemoglobin; Ferritin; CBC indices; Libya